Examining the Link between Math Anxiety and Math Performance in Colombian Students (2016)
This study examines the link between math anxiety and math performance in a group of Colombian students. A total of 296 students between 8 and 16 years of age took part in this study. Analyses by gender and grade were conducted, while controlling for other types of anxiety (i.e., general and test anxiety). In line with that reported in other countries, a negative correlation was found between performance in mathematics and math anxiety. Importantly, this trend was stronger in girls than in boys. Given the limited number of studies exploring the relationship between math anxiety and math performance in Latin America and, particularly, in Colombia, this study fills an important gap in the literature. The results are particularly relevant in view of the poor performance of Colombian students in mathematics, revealed by the most recent PISA reports.